The Stratification of Universities Revisited: Status, Followers, and the Shape of National Hierarchies - Pizarro Milian, Roger; Zarifa, David (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2023)
It is generally accepted that Canadian universities are less stratified than their southern neighbours, a hypothesis popularized in the mid-2000s and verified by subsequent comparative empirical research. Through this piece, we revisit the Canadian “flatness” hypothesis, embracing a more sociological definition of status hierarchies and using social media followers as a focal proxy for status. Despite our theoretically based skepticism, adoption of an alternative status proxy, and use of more recent data, our analyses validate the flatness hypothesis. We theorize the implications of these findings, and our novel approach, for the study of organizational stratification in higher education.